Traumatic C7-T1 spondyloptosis without neurological injury: Case review and surgical management - Christopher Payne; Michael J. Gigliotti; Alejandro Castellvi; Alexander Yu; Philip S. Lee (Interdisciplinary Neurosurgery, 2020)
Background and importance: Cervical spondyloptosis is defined as >100% anterior or posterior subluxation of the spondyloptotic vertebral body on a subadjacent vertebral body. This often results in severe neurologic deficits; however, this occasionally has been reported in neurologically intact patients. There have only been two cases of spondyloptosis at the cervicothoracic junction reported in the research literature. Clinical presentation: A 63-year-old male had complete spondyloptosis at C7-T1 after a ground level fall. The patient did not present with neurologic deficits. The patient underwent a C2-T3 posterior fusion with C3-T1 laminectomy. Post-operative course was complicated by superficial dehiscence and infection with methicillin-sensitive Staphylococcus aureus, which was managed with incision and drainage along with one week of Cephalexin. At last follow-up, the patient was doing clinically well. Conclusion: Early operative intervention without cervical traction and closed reduction pre-operatively in a patient with cervicothoracic spondyloptosis resulted in a good clinical outcome. Keywords: Spondyloptosis, Spine, Neurosurgery